2010
DOI: 10.1007/s10800-010-0227-2
|View full text |Cite
|
Sign up to set email alerts
|

3,4-Dimethoxybenzaldehydethiosemicarbazone as corrosion inhibitor for aged 18 Ni 250 grade maraging steel in 0.5 M sulfuric acid

Abstract: The corrosion inhibition of the aged 18 Ni 250 grade maraging steel in 0.5 M sulfuric acid by 3,4-dimethoxybenzaldehydethiosemicarbazone(DMBTSC) has been investigated by potentiodynamic polarization and electrochemical impedance spectroscopy(EIS) techniques. The inhibition efficiency increased with the increase in inhibitor concentration and decreased with the increase in temperature. Polarization curves indicated mixed type inhibition behavior affecting both cathodic and anodic corrosion currents. The thermod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 59 publications
(58 reference statements)
0
16
1
Order By: Relevance
“…Thus, the decrease in C dl value is attributed to the replacement of the adsorbed water molecules at the surface metal by the inhibitor having lower dielectric constant (39). Also, the decrease in surface area which acts as a site for charging may be considered as another reason for the C dl decrease (40). These points suggest that the role of inhibitor molecules is preceded by its adsorption at the metal-solution interface.…”
Section: Electrochemical Impedance Spectroscopy)mentioning
confidence: 97%
“…Thus, the decrease in C dl value is attributed to the replacement of the adsorbed water molecules at the surface metal by the inhibitor having lower dielectric constant (39). Also, the decrease in surface area which acts as a site for charging may be considered as another reason for the C dl decrease (40). These points suggest that the role of inhibitor molecules is preceded by its adsorption at the metal-solution interface.…”
Section: Electrochemical Impedance Spectroscopy)mentioning
confidence: 97%
“…Activation energy (E a ) for the corrosion process of the welded maraging steel in sulfuric acid was calculated from the Arrhenius equation (Eq. (8)) as in [3,4]: (8) where B is a constant that depends on the metal type, and R is the universal gas constant. The plot of ln(v corr ) versus reciprocal of absolute temperature (1/T) gives a straight line with the slope = -E a /R, from which the activation energy values for the corrosion process were calculated.…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…The unique property of being weldable in the solution ized condition followed by a low temperature (480°C) post weld maraging treatment makes these steels attractive for fabrication of large structures [2]. Accord ing to available literature, atmospheric exposure of 18 Ni maraging steel leads to its corrosion in a uniform manner and makes it completely rust covered [3,4]. Bellanger et al [5] have reported that the corrosion behavior of maraging steel at the corrosion potential depends on pH and intermediates remaining on the maraging steel surface in the active region favoring the 1 The article is published in the original.…”
Section: Introductionmentioning
confidence: 99%
“…Some works have revealed that the inhibition efficiency of these compounds is much higher than the corresponding effect obtained with amines and aldehydes. This phenomenon is attributed to the presence of the imine group (-C5 5N-) in the molecules [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%